The motivation for learning the history of cuba in the mining engineering career from virtual learning environments - Paz González, Alexander; Rodríguez Maden, Ángela Lilia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The teaching-learning process of the History of Cuba acquires singular relevance in the Mining Engineering career. This has as a graduate a mining engineer with a broad profile, who is scientifically and technically trained to carry out works of rational exploitation of mineral resources. . Changes are very fast and education must make it easier for students to adapt to them. For this, the use of a virtual learning environment or EVA can be a very useful tool.